2023
DOI: 10.1101/2023.11.01.564448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LMO3 is a suppressor of the basal-like/squamous PDAC subtype and reduces disease aggressiveness of pancreatic cancer through glycerol 3-phosphate metabolism

Yuuki Ohara,
Amanda J. Craig,
Huaitian Liu
et al.

Abstract: Pancreatic ductal adenocarcinoma (PDAC) encompasses diverse molecular subtypes, including the classical/progenitor and basal-like/squamous subtypes, each exhibiting distinct characteristics, with the latter known for its aggressiveness. We employed an integrative approach combining transcriptomic and metabolomic analyses to pinpoint potential genes contributing to the basal-like/squamous subtype differentiation. Applying this approach to our NCI-UMD-German and a validation cohort, we identified LIM Domain Only… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Applying pathway enrichment analysis using MetaboAnalyst 5.0 (25), we noticed that ADRA2A-overexpressing Panc 10.05 cells exhibited diminished amino acid metabolism (Figure 4D). Our findings corroborate earlier research conducted by our group, indicating that the basallike/squamous subtype fosters amino acid metabolism, whereas the classical/progenitor subtype suppresses it (17,23,24). Additionally, ADRA2A-high tumors and ADRA2A-overexpressing Panc 10.05 cells showed the downregulation of carnitine/acylcarnitines.…”
Section: Pdacsupporting
confidence: 93%
See 4 more Smart Citations
“…Applying pathway enrichment analysis using MetaboAnalyst 5.0 (25), we noticed that ADRA2A-overexpressing Panc 10.05 cells exhibited diminished amino acid metabolism (Figure 4D). Our findings corroborate earlier research conducted by our group, indicating that the basallike/squamous subtype fosters amino acid metabolism, whereas the classical/progenitor subtype suppresses it (17,23,24). Additionally, ADRA2A-high tumors and ADRA2A-overexpressing Panc 10.05 cells showed the downregulation of carnitine/acylcarnitines.…”
Section: Pdacsupporting
confidence: 93%
“…Recognizing the biological similarity, we grouped unclassified and classical/progenitor subtypes into a unified group termed "unified classical/progenitor subtype" (23). LIM Domain Only 3 (LMO3) downregulated both basal-like genes and classical genes developed by Moffitt et al (4) to induce the unified classical/progenitor subtype (23). However, the current study revealed that ADRA2A upregulates the classical genes while downregulating the basal-like genes to promote classical/progenitor subtype differentiation.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations